VET in Europe - Country report Austria - Tritscher-Archan, Sabine [Verfasser]; Grün, Gabriele [Verfasser]; Nowak, Sabine [Verfasser]; Weiß, Silvia [Verfasser] (My University, 2012)
"This report provides a picture of the Austrian vocational education and training (VET) system. It covers a broad range of topics: Following introductory background information about the political and socio-economic context in Austria, the second chapter describes the Austrian education system. It presents VET programmes both at school level and in higher education as well as those outside the formal education system. The third chapter focuses on the instruments and processes to match qualification supply and demand. It describes how qualifications are defined and what processes take place in this connection. The fourth and final chapter deals with the financial incentives given to encourage participation in VET. In addition, this chapter informs about educational counselling and career guidance services." (Hrsg., BIBB-Doku)
Keywords: S System beruflicher Bildung; I 2.2.1 Westeuropa; Berufsbildungssystem; Bildungsangebot; Betriebliche Berufsausbildung; Schulische Berufsausbildung; Berufliche Weiterbildung; Bildungsfinanzierung; Bildungsberatung; Österreich